Integrated Test Examination as a Means of Improving and Control Quality of Physical Education - Kharchenko, Larysa; Denisova, Lolita; Харченко, Лариса; Денисова, Лоліта (Східноєвропейський національний університет ім. Лесі Українки, 2012)
In this article are examined the questions of improving and control of the teaching quality by implementation of the complex integrated testing for the fourth-year students of the National University of Physical Education and Sport of Ukraine, educationally-qualifying level Bachelor, field of knowledge «Physical Education, Sport and Human Health». The special attention is spared to the questions of improving the forms and methods of control of students’ educational achievements. The stages of the implementation of integrated testing, and the structure and contents of the test tasks are described in details. It is noted that the implementation of a complex integrated testing has vastly increased the efficiency of preparation of skilled specialists in the field of physical culture and sports. У статті розглянуто питання підвищення та контролю якості навчання через упровадження комплексного інтегрованого тестування для студентів галузі знань «Фізичне виховання, спорт і здоров’я людини» освітньо- кваліфікаційного рівня бакалавра, які навчаються на четвертому курсі Національного університету фізичного виховання і спорту України. Особливу увагу приділено питанням удосконалення форм та методів контролю навчальних досягнень студентів. Докладно описано етапи впровадження комплексного тестування, а також структуру й зміст тестових завдань. Відзначено, що впровадження комплексного інтегрованого тестування істотно підвищило ефективність підготовки кваліфікованих фахівців галузі фізичної культури та спорту.
Tестування як засіб покращення якості фізичного виховання
Keywords: education quality; quality of specialists’ training; testing; computer technology; integrated test examination; якість навчання; якість підготовки фахівців; тестування; комп'ютерні технології; тестовий інтегрований іспит